Mucosal Mast Cells Contribution in Intestinal Defense of Chickens (Gallus domesticus) Infected Naturally by Ascaridia galli - Ummu Balqis; Masda Admi; Darmawi Darmawi; Muhammad Hambal (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
This study was aimed at finding out the investigation of mucosal mast cells   in intestines of chicken  that  were  naturally  infected  by  Ascaridia galli.  Amount  of  ten  intestine  of  freshly slaughtered chickens (Gallus domesticus) found from local abatoir in Banda Aceh were divided into two groups containing five intestines of each. Mucosal mast cells count were done of which histologic slides were made in stained serial histological sections with Alcian blue (pH 0,3) and Safranin-O (pH 0,1) of the intestines. The result showed that the mucosal mast cells increased significantly (P 0.05) in intestines of chickens infected naturally by survival A. galli adult worms. It was concluded that the intestinal defense of chickens against parasite infection is associated with the mucosal mast cells contribution by creating an environment hostile to the establishment and survival of intestinal nematodes, A. galli.